Tsunami! - Kajikawa, Kimiko; Young, Ed (New York : Philomel Books, 2009)
A wealthy man in a Japanese village, who everyone calls Ojiisan, which means grandfather, sets fire to his rice fields to warn the innocent people of an approaching tsunami.
Pub Weekly
School Library Journal starred
Wilson's Children
Booklist, November 2008
Bulletin (Center for Children's books), January 2009
Horn Book, October 2009
Keywords: Folklore -- Japan; Tsunamis -- Folklore; Folklore -- Japan; Tsunamis -- Folklore; Folklore -- Japan; Tsunamis -- Folklore